Akupresure untuk Mengurangi Nyeri Haid pada Remaja Putri - Emilia Nur Achmada; Sri Astuti; Sodiyahi; Cahyaningrum (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2023)
dolescence is a dynamic developmental phase in an individual's life, one of the typical signs of adolescence is the onset of puberty. Dysmenorrhea is pain or tenderness in the lower abdomen that occurs when women experience their menstrual cycle. To reduce menstrual pain can be done using pharmacological and non-pharmacological methods. One of the non-pharmacological therapies is acupressure therapy. Acupressure is a treatment system that uses pressure on certain points on the body.Results of an assessment in a lecture environment, with 21 female students experiencing menstrual pain. In connection with this problem, the community service program at the Borneo Medistra campus provides a solution to the problem of menstrual pain in young women by carrying out community service activities regarding acupressure to reduce menstrual pain. The aim of this activity is to increase young women's knowledge about acupressure to reduce menstrual pain. The results of this activity show that the knowledge of young women increased after carrying out community service activities with education about acupressure to reduce dysmenorrhea pain. Community service activities were carried out on November 30 2023 in level 1 classrooms, attended by 21 female students. Activities are carried out in 3 stages, namely pretest, material delivery and posttest. The results of the activity revealed that before being given community service regarding acupressure to reduce menstrual pain in young women, the distribution of scores among female students at the Borneo Medistra Polytechnic mostly had poor knowledge, as many as 14 young women (71%) and good knowledge as many as 7 young women (29%) After being given counseling about acupressure massage, the distribution of 14 female students with poor knowledge increased to 18 female students (92%) who had very good knowledge and 3 female students (8%) who had sufficient knowledge. This shows that there is an increase in female students' knowledge after being given knowledge about dysmenorrhea and acupressure massage.   Abstrak Masa remaja terjadi suatu fase perkembangan yang dinamis dalam kehidupan seorang individu, salah satu tanda yang khas pada remaja adalah terjadinya pubertas. Dismenorea adalah rasa sakit atau nyeri pada bagian bawah perut yang terjadi saat wanita mengalami siklus menstruasi. Untuk mengurangi nyeri haid dapat dilakukan dengan cara farmakologi dan non farmakologi. salah satu terapi non farmakologi adalah terapi akupresure. Akupresure adalah sistem pengobatan dengan cara menekan-nekan pada titik-titik tertentu pada tubuh. Hasil pengkajian di lingkungan perkuliahan, dengan 21 mahasiswi yang mengalami nyeri haid. Berkaitan dengan masalah tersebut, program pengabdian masyarakat dikampus Borneo Medistra memberi solusi untuk permasalahan nyeri haid pada remaja putri dengan melaksanakan kegiatan pengabdian masyarakat tentang akupresure untuk mengurangi nyeri haid. Tujuan dari kegiatan ini adalah meningkatkan pengetahuan remaja putri tentang akupresure untuk mengurangi nyeri haid. Dari hasil kegiatan ini menunjukkan bahwa pengetahuan remaja putri meningkat setelah dilakukan kegiatan pengabdian  masyarakat dengan penyuluhan tentang akupresure untuk mengurangi nyeri dismenore. Kegiatan pengabdian masyarakat dilaksanakan pada tanggal 30 November 2023 di ruangan kelas tingkat 1 dengan dihadiri 21 Mahasiswi . Kegiatan dilakukan melalui 3 tahap yaitu pretest, penyampaian materi dan posttest. Hasil kegiatan diketahui bahwa sebelum diberi pengabdian masyarakat tentang akupresure untuk mengurangi nyeri haid pada remaja putri distribusi nilai dari mahasiswi di Politeknik Borneo Medistra sebagian besar memiliki pengetahuan kurang, sebanyak 14 remaja putri (71%) dan berpengetahuan baik sebanyak 7 remaja putri (29%) setelah diberikan penyuluhan tentang pijat akupresure distribusi dari 14 mahasiswi pengetahuan kurang naik menjadi 18 remaja putri (92%) berpengetahuan sangat baik dan 3 remaja putri (8%) berpengetahuan cukup. Hal ini menunjukkan bahwa terdapat peningkatan pengetahuan mahasiswi setelah diberikan pengetahuan tentang dismenore dan pijat akupresure.